Determination of the Δ++ magnetic dipole moment - López Castro, G. (2001)
We study the elastic and radiative π+p scattering within a full dynamical model which incorporates the finite width effects of the Δ++. The scattering amplitudes are invariant under contact transformations of the spin 3/2 field and gauge-invariance is fulfilled for the radiative case. The pole parameters of the Δ++ obtained from the elastic cross section are mΔ = (1211.2±0.4) MeV and ΓΔ = (88.2±0.4) MeV. From a fit to the most sensitive observables in radiative π+p scattering, we obtain μΔ = (6.14±0.51)e/2mp for the magnetic dipole moment of the Δ++.